Issues in quality engineering research - Hassan, Adnan; Nabi Baksh, Mohd Shariff; M. Shaharoun, Awaluddin (Emerald Group Publishing Limited, 2000)
he field of quality has undergone significant changes as reflected by changes in its definition, paradigms, approaches, techniques, and scope of application. This paper reviews emerging trends and issues focusing on quality engineering. Changes in customer expectation have driven the changes in the technology of design and manufacturing, which is becoming more important in satisfying individual customer expectations. This also calls for special attention to the engineering aspects of quality. Brief reviews on recent advances in the prominent quality tools such as statistical process control, quality function deployment, and design of experiment are reported. General trends in quality engineering research show the tools are being enhanced, integrated, computerized and broaden their application bases, where possible opportunities for further investigation are indicated. Among others these include contributions in multiple-response optimization, intelligent quality systems, multivariate SPC, and practical and simple guidelines for actual implementation of various tools.